Utilization of dental health-care services by accredited social health activist and anganwadi workers in lucknow district: A cross-sectional study - Dyashwari Devi Khoisnam; L Vamsi Krishna Reddy; Pooja M Sinha; B S Goutham; Sonali Saha (Wolters Kluwer Medknow Publications, 2022)
Background: Accredited Social Health Activists (ASHAs) and Anganwadi workers are grassroots-level health activists who are involved in health education and community mobilization and form a bond between the community and the primary health-care delivery system in India. The cross-sectional study was conducted to assess the dental health-care utilization and to estimate the dentition and periodontal status of ASHA and Anganwadi workers. Materials and Methods: The study was conducted at the primary health centers and subcenters of Lucknow District. ASHA and Anganwadi workers presented on the day of the examination were included in the study. The study pro forma was used to record demographic details and dental utilization. Dentition status and periodontal status were used to record dental caries and periodontal status using the World Health Organization Oral Health Assessment Form 2013. Data were analyzed using the SPSS version 21; descriptive statistics, Chi-square test, and regression analysis were used to assess factors related to health-care utilization and P < 0.005 was considered statistically significant. Results: The final study sample comprised 500 health-care workers (220 ASHA and 280 Anganwadi workers). Among the study population, 30% utilized dental services and was found to be statistically significant with age, occupation, and oral findings. However, 56.0% had both dental caries and periodontal diseases followed by dental caries‒32.0%, periodontal disease‒8.0%. There was a significant difference (P < 0.005) in the proportion of dental care utilization and oral diseases among participants. Conclusions: The dental care utilization was found to be short and is not comparative to the diseases among participants.